2012
DOI: 10.1590/s0104-66322012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Antiwear and antioxidant studies of cardanol phosphate ester additives

Abstract: -In the search for new applications and products derived from Cashew Nut Shell Liquid (CNSL), we report herein the synthesis and characterization (GC/MS and 1 H, 13 C, and 31 P NMR) of four phosphate esters derived from hydrogenated cardanol, including their applications as antiwear additives for diesel (S500) and as antioxidant additives for mineral oils, evaluated through the HFRR test and oxidative stability analyses, respectively. The results obtained showed very good to excellent performances promoted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Comparison between diphenyl-and diethylphosphate esters of saturated and unsaturated cardanol showed that the phenyl derivatives have a better thermal stability than the ethyl derivatives. 242,249 An interesting study 245 also evaluated the potential of a tris(cardanol) phosphate ester (Figure 7) compared to other phenyl-or ethyl-derivatives. This compound did not display significant differences with other phosphate esters.…”
Section: Applications Of Phosphorylated Cnsl Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison between diphenyl-and diethylphosphate esters of saturated and unsaturated cardanol showed that the phenyl derivatives have a better thermal stability than the ethyl derivatives. 242,249 An interesting study 245 also evaluated the potential of a tris(cardanol) phosphate ester (Figure 7) compared to other phenyl-or ethyl-derivatives. This compound did not display significant differences with other phosphate esters.…”
Section: Applications Of Phosphorylated Cnsl Derivativesmentioning
confidence: 99%
“…However, thiophosphate esters were found to have an even higher antioxidant effect than phosphate esters. 245 The authors employed an oxidative stability analysis, in which the mineral oils samples formulated with the phosphorylated cardanol additive were heated at 100 °C for 164 hours in an O 2 flow of 1000 ml/h. Cardol has the same structure than cardanol but possess a second phenolic hydroxy on the meta position.…”
Section: Applications Of Phosphorylated Cnsl Derivativesmentioning
confidence: 99%
“…Although such peculiar chemical structure allowed the development of many technological products from cardanol [ 9 ] to the best of our knowledge, there is only one published work on anti‐wear additives derived from cardanol, [ 10 ] no other group has further explored the potential of CNSL in the field of lubrication science.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Cardanol is a yellow, pale liquid composed of four meta-alkyl phenols differing by degrees of unsaturation of the aliphatic chain (Figure 1): saturated chains (SC) 7 %, monoolefinic (MO) 48 %, diolefinic (DO) 16 % and triolefinic (TO) 29 % of chains. 7,8 The phenolic character of cardanol and the unsaturations in its hydrophobic alkyl side chain attracted attention for the various possible chemical modifications they allow, and make it an important reactive starting material having potential industrial applications such as antioxidants, 9,10 plasticizers, 11,12 flame retardants, 13,14,15 and resins. [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%